Magnetic storage the medium that wouldn't die. - Comerford, R. (IEEE spectrum)
Computers have been storing data magnetically on disks for close to a half century. Yet in the last few years, the ability to pack data onto a surface using this supposedly mature technology has advanced by leaps and bounds. Starting in 1997 with IBM's introduction of the first giant magnetoresistive read-and-write head, density has been doubling every year. Researchers now expect disk storage density to continue doubling at least until 2005. Breakthroughs in the technology by Fujitsu, AT&T Bell Laboratories and TeraStor are discussed in this article.